Transnational Jihadism and the Insurgency in Cabo Delgado, Mozambique - Bonate, Liazzat J. K. (2022)
This paper analyzes the conflict in Cabo Delgado against transnational jihadism, an ideology and political movement that takes hold of local grievances, especially against the state, triggering insurgency or channeling existing resistance. The conflict also represents a resistance against the Western-dominated global order. In its first part, the article discusses the concept and history of transnational jihadism, highlighting the changes in the ideology and actions of its protagonists, and its geographical expansion worldwide. The second part analyzes the socio-political and economic context of Cabo Delgado that contributed to the onset of insurgency, highlighting the resistance against the Mozambican state and against Western hegemony in the form of extractivism driven by transnational corporations that came to Cabo Delgado beginning in 2010.